Pengaruh Waktu Pemerahan dan Tingkat Laktasi terhadap Kualitas Susu Sapi Perah Peranakan Fries Holstein - Mardalena, Mardalena (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2008)
This study intended to  know the  difference of milk quality result of pressing out of evening and morning at level of lactation (I, II and III) of Fries Holstein dairy cattle. Experimental design used in this experiment  was Complete  Randomized  Design  (CRD)  Factorial 2x3 Pattern  by  10  times replication. The result indicated that quality of milk at pressing out of morning were fat rate (3,17%), dry materials rate ( 12,206%) and protein rate ( 3,583%)was lower  than  pressing out of evening which were  fat rate ( 3,69%), dry materials rate ( 12,527%) and protein rate ( 3,613%). Conclusion of this research was  the quality of milk when pressing out morning  lower than  evening. Level of lactation  didn’t  influence the quality of milk.